Canine Gouging: A Taboo Resurfacing in Migrant Urban Population - Anila Virani Noman; Ferranti Wong; Ravikiran Ramakrishna Pawar (Case Reports in Dentistry)
Cosmopolitan cities have become a pool of migrants from different parts of the world, who carry their cultural beliefs and superstitions with them around the globe. Canine gouging is a kind of infant oral mutilation (IOM) which is widely practiced among rural population of Africa where the primary tooth bud of the deciduous canine is enucleated. The belief is that the life threatening illnesses in children like vomiting, diarrhoea, and fevers are caused by worms which infest on tooth buds. This case report is of a 15-year-old Somalian born boy, who presented at the dental institute with intermittent pain in his lower right permanent canine which was associated with a discharging intra oral buccal sinus. The tooth was endodontically treated and then restored with composite. General dental practitioners need to be vigilant when encountered with tooth presenting unusual morphology, unilateral missing tooth, and shift in the midline due to early loss of deciduous/permanent canines. Identification of any such dental mutilation practice will need further counselling of the individual and family members. It is the duty of every dental professional to educate and safeguard the oral and dental health of general public.